Effects of Hyperglycemia on Angiogenesis in Human Placental Endothelial Cells - Yanik, Turkan; Katirci, Ertan; Simsek, Mehmet; Korgun, Emin Turkay; Kipmen-Korgun, Dijle (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
The placenta is a temporary organ that provides communication between the mother and fetus. Maternal diabetes and abnormal placental angiogenesis may be linked. We investigated the angiogenesis mechanism resulting from VEGF and glucose stimulation in PECs obtained from human term placenta. Immunohistochemistry was performed to characterize PECs obtained from human term placenta. D-glucose was added to the medium containing PECs to establish normoglycemic and hyperglycemic conditions. The expression levels of VEGF, VEGFR-1 and VEGFR-2 genes and proteins in PECs from the control and experimental groups were analyzed by RT-PCR and Western blotting, respectively. With 48-hours incubation, gene expressions increased due to hyperglycemia, while protein levels increased due to the combined effect of VEGF and hyperglycemia. While VEGFR-2 gene expression and protein amounts increased in 24-hours due to the combined effect of VEGF and hyperglycemia, the effect of VEGF stimulation and glucose level on VEGFR-2 decreased in 48-hour incubation with time. VEGF, VEGFR-1 and VEGFR-2 genes and proteins were affected by hyperglycemic conditions in PECs. Hyperglycemia occurring in various conditions such as gestational diabetes mellitus and diabetes mellitus may affect VEGF, VEGFR-1 and VEGFR-2 genes and proteins of PECs derived from human term placenta.
Keywords: placenta; angiogenesis; hyperglycemia; pregnancy; cell culture techniques